Toxic substances in the household - cases of poisoning, therapy, complications - Wilk, Joanna; Kubicka, Magdalena; Dębiec, Paweł; Szydłowski, Przemysław; Makarewicz, Magdalena; Porzak, Mikołaj; Szyłkajtis, Natalia (Journal of Education, Health and Sport, 2023)
There are many toxic substances used in our houses. Rodent poisons are not the most common group of substances, but cases of poisoning still occur. Long-acting anticoagulant rodenticides, also called superwarfarins, are known for their greater potency, longer half-life and delayed onset of symptoms. Cases of superwarfarin poisoning can pose a diagnostic and clinical challenge due to a wide array of presentations and prolonged severe coagulopathy requiring months of high-dose oral vitamin K therapy. The most common presentation of long-acting anticoagulant rodenticide poisoning is mucocutaneous bleeding, with other common presentations including haematuria, gingival bleeding, epistaxis and gastrointestinal bleeding.We discuss a case of self-poisoning with long-acting anticoagulant rodenticides with a little presentation of sympthoms and disscus about another cases based on the found articles.